Validation of screening examinations of the ureteral orifices in dogs: Comparison of ultrasonography with dissection. (August 2015) - Balogh, O.; Degrandi, F.; Hässig, M.; Reichler, I.M.
Highlights: Standardizing ultrasonography measurements of ureteral openings in dogs is proposed. Measurements at two bladder filling stages were compared to dissection. The left ureterovesical–vesicourethral distance was affected by bladder distension. Measurements by ultrasonography were in agreement with dissection. Abstract: In dogs, ultrasonography is performed to locate the ureteral orifices in the urinary bladder, but reference values for their normal location using this technique are missing. In this study, the ureterovesical–vesicourethral and inter-ureterovesical distances were determined in 20 freshly euthanized medium size dogs by detecting artificially produced ureteral jets in color-flow Doppler ultrasonography at two different bladder volumes, and comparing them to manual measurements in the dissected bladder. All distances determined by ultrasonography were in agreement with values found by dissection (P ≥ 0.100). With increasing bladder volume only the left ureterovesical–vesicourethral distance changed (P = 0.041). The right ureteral opening was more cranial than the left in 16 dogs. The inter-ureterovesical distances differed by gender (P = 0.016), but spay/neuter status had no influence (P ≥ 0.847). In conclusion, ultrasonography is a reliable modality for screening ureteral orifices in medium size dogs and agrees with anatomical findings.